2014
DOI: 10.1007/s10823-014-9241-x
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and Gender Differences in Coping Strategies Between Caucasian American and Korean American Older People

Abstract: Coping strategies have significant effects on older people's health. This study examined whether gender and ethnic differences influence the coping strategies chosen by older adults when they encounter daily life stressors. Data were collected from 444 community-dwelling people over the age of 65, including 238 Caucasian Americans and 206 Korean Americans. Results showed significant differences between the two groups. Korean Americans had higher scores on problem and emotion-focused coping strategies as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 45 publications
4
23
0
2
Order By: Relevance
“…Most studies adopted quantitative-correlational designs, most of which were cross-sectional (n = 9; e.g., Mossakowski & Zhang, 2014) and one of which was longitudinal (Kiang & Buchanan, 2014); the rest used qualitative designs (interview or case study, n = 5; e.g., Connor & Miller, 2014) The two articles in the category of coping in the context of health-related problems highlighted specific coping strategies for certain diseases, including asthma or chronic obstructive pulmonary disease (S. K. and breast cancer (Lim, 2014). The two articles about coping strategies examined whether gender, ethnicity (H. Lee & Mason, 2014) and collective self-esteem related to coping strategies. For example, H. Lee and Mason (2014) found that Korean Americans (vs. Caucasians) scored higher on problem-focused, emotion-focused, and avoidant coping strategies; women (vs. men) utilized more planning, religion, and denial coping strategies.…”
Section: Viruses: Hepatitis B Virus (Hbv) Immunodeficiency Virus (Himentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies adopted quantitative-correlational designs, most of which were cross-sectional (n = 9; e.g., Mossakowski & Zhang, 2014) and one of which was longitudinal (Kiang & Buchanan, 2014); the rest used qualitative designs (interview or case study, n = 5; e.g., Connor & Miller, 2014) The two articles in the category of coping in the context of health-related problems highlighted specific coping strategies for certain diseases, including asthma or chronic obstructive pulmonary disease (S. K. and breast cancer (Lim, 2014). The two articles about coping strategies examined whether gender, ethnicity (H. Lee & Mason, 2014) and collective self-esteem related to coping strategies. For example, H. Lee and Mason (2014) found that Korean Americans (vs. Caucasians) scored higher on problem-focused, emotion-focused, and avoidant coping strategies; women (vs. men) utilized more planning, religion, and denial coping strategies.…”
Section: Viruses: Hepatitis B Virus (Hbv) Immunodeficiency Virus (Himentioning
confidence: 99%
“…The two articles about coping strategies examined whether gender, ethnicity (H. Lee & Mason, 2014) and collective self-esteem related to coping strategies. For example, H. Lee and Mason (2014) found that Korean Americans (vs. Caucasians) scored higher on problem-focused, emotion-focused, and avoidant coping strategies; women (vs. men) utilized more planning, religion, and denial coping strategies. Lee & GlenMaye, 2014;Woo, Lee, & Hong, 2014).…”
Section: Viruses: Hepatitis B Virus (Hbv) Immunodeficiency Virus (Himentioning
confidence: 99%
“…Estos resultados pueden responder a las variables culturales propias de la idiosincrasia e historia de Paraguay, ya mencionadas. En una muestra de personas mayores, se observaron evidentes diferencias dependiendo del sexo y de la cultura (Lee & Mason, 2014), sin embargo, estas podrían deberse a que las muestras son menos similares a las utilizadas en el presente estudio.…”
Section: Discusión Y Conclusionesunclassified
“…La literatura muestra que las formas de afrontamiento pueden variar durante la adolescencia en función de algunas variables personales, en particular, del sexo y la edad (Frydenberg & Lewis, 2000a;Seiffge-Krenke, 2011;Seiffge-Krenke, Aunola, & Nurmi, 2009), debido a su asociación a cambios en el desarrollo y también a factores contextuales, como la cultura (Lee & Mason, 2014;Samper, Tur, Mestre, & Cortés, 2008;Urzúa, Basabe, Pizarro, & Ferrer, 2017). En cuanto al sexo, se reporta que las chicas, en general, tienden a utilizar una mayor variedad de estrategias de afrontamiento, siendo las de mayor uso las relacionadas con la búsqueda de apoyo social, mientras que los chicos reportan el uso de algunas estrategias de distanciamiento del problema, como buscar actividades relajantes o distraerse (Barcelata et al, 2016;Connor-Smith & Compas, 2004;Frydenberg & Lewis, 2000b;Seiffge-Krenke, 2000).…”
unclassified
“…13 Overall, given that people with dementia likely face a wide range of stressful situations, such as loss of friends and family, loneliness, cognitive decline, and health problems, they need to adjust their coping strategies to deal with the mulitple difficulties they face. 14 Patients' ability to cope has been shown to directly affect their QOL. 15 Previous research on AD indicated that patients preserve their spirituality regardless of the decline in their cognitive functions.…”
Section: Introductionmentioning
confidence: 99%